A Bibliometric Analysis of Fintech Trends: An Empirical Investigation - Girish Garg; Mohd Shamshad; Nikita Gauhar; Mosab I. Tabash; Basem Hamouri; Linda Nalini Daniel (International Journal of Financial Studies, 2023)
Financial technology, or Fintech, has captured the attention of scholars, students, and institutions across worldwide for over a decade. With a plethora of new financial services, products, and innovative methods to engage with clients, the impact of technology on the financial sector has been extensively studied. This research paper provides a summary of scientific research on FinTech by using bibliometric analysis. Using the Scopus database, the paper analyzed 665 publications and identified research gaps and new study topics through “VOS-Viewer” software and “Biblioshiny” using RStudio. The study focused on FinTech’s functions and research constraints in digital finance by assessing citation links between the most significant articles. The findings provide a starting point for further investigation and offer opportunities for researchers to expand their expertise in exciting and innovative studies. Overall, this study seeks to help researchers discover new avenues for exploration in Fintech while advancing their present understanding. There exists much scope in the area of Digital Lending, Supply Chain Finance, the Internet of Things, and RoboAdvisers.